Strengthening and toughening austenitic steel by introducing gradient martensite via cyclic forward/reverse torsion. (5th April 2018) - Guo, Ning; Zhang, Zhimin; Dong, Qingshan; Yu, Hongbing; Song, Bo; Chai, Linjiang; Liu, Cong; Yao, Zhongwen; Daymond, Mark R.
Abstract: Converting austenite to martensite is a very effective and low-cost strategy for steel strengthening, but it results in a significant loss of ductility. In this study, we propose a novel method which simultaneously strengthens and toughens austenitic steels by introducing a gradient of martensite phase. We find that a gradient of deformation-induced martensite (α′-M) particles, with a volume fraction increasing from core to surface can be obtained in cylindrical AISI 304 stainless steel (304 SS) rods by applying free-end-torsion (FET). We compared the microstructures and tensile properties of gradient-structured 304 SS prepared by unidirectional-torsion (UT) and cyclic forward/reverse torsion (CFRT). It appears that piled-up dislocations formed near the core region during FET processing play a key role in the subsequent tensile deformation, and control the strain-hardening ability of the FET treated samples. The gradient α′-M enhances the strength of the surface layer and improves the tensile properties of the FET treated samples as a whole. Compared to UT, CFRT is more effective in inducing martensitic transformation, and enhances the gradient distribution of the α′-M. These findings provide a pathway for developing high strength and good ductility steels and other alloyed metals via gradient distributed second phase particles. Graphical abstract: Highlights: Gradient BCT structured martensite (α′-M) particles can be introduced into commercial 304 SS by free-end-torsion. Cyclic forward/reverse torsion (CFRT) is more effective in enhancing the gradient distribution of α′-M compared to unidirectional-torsion (UT). Gliding Shockley partial dislocations (GSPDs) play a key role in deformation-induced martensite transformation. Gradient α′-M enhances surface strength and improves overall tensile properties of the 304 ss.